The Role of Price, Location, and Satisfaction in Making Bird Purchase Decisions at the Jatinegara Bird Market in East Jakarta - Madiistriyatno, Harris (Raudhah Publisher, 2025)
This study aims to analyze the role of price, location, and satisfaction in bird purchase decision making at Jatinegara Bird Market, East Jakarta. This study uses a qualitative approach with a descriptive method. Data was obtained through in-depth interviews with buyers, traders, and market managers, as well as direct observation in the field. The results of the study show that price is the main factor that influences the purchase decision, especially for buyers who have a limited budget. The strategic and easily accessible location of the market also plays an important role in attracting buyers, especially from the area around Jakarta. In addition, buyer satisfaction with the quality of the birds, merchant service, and market atmosphere has a significant impact on consumer loyalty and the decision to make a repeat purchase. This study concludes that price, location, and satisfaction interact with each other in shaping the decision to buy birds at the Jatinegara Bird Market. The recommendations of this study include competitive price management, improvement of market facilities, and optimization of merchant services to increase consumer satisfaction.